Crystalline Covalent Triazine Frameworks with Fibrous Morphology via a Low‐Temperature Polycondensation of Planar Monomer. Issue 20 (14th April 2022) - Liu, Jing; Liu, Manying; Wang, Xueqing; Wang, Xiaoyan; Tan, Bien
Abstract: The morphology regulation of covalent triazine frameworks (CTFs) is a great challenge, which may be due to the difficulty in controlling its morphology by traditional synthesis methods. Herein, a general approach to fabricate morphology controllable CTFs by a mild polycondensation reaction in mixed solvents without any templating agents is reported. As a proof of concept, a type of crystalline CTFs with distinctive fibrous morphology (MS‐F‐CTF‐1) (MS: Mixed Solvent; F: Fibrous Morphology) is developed by adjusting the ratio of mixed solvents to control the solubility of monomers, so that the nucleation, crystal growth, and subsequent self‐assembly are controlled, which facilitates the formation of fibrous morphology. The resultant crystalline MS‐F‐CTF‐1 shows uniform fibrous morphology with a diameter of about 100 nm and a length of several micrometers. Notably, the fibrous morphology of CTFs can efficiently improve the photocatalytic hydrogen evolution performance, in which the hydrogen evolution rate can be boosted by about two times in comparison to block ones. Abstract : A facile strategy to fabricate morphology controllable covalent triazine frameworks (CTFs) by a mild polycondensation reaction in mixed solvents is reported. The resultant crystalline CTFs exhibits fibrous morphology, which endows them with high charge transfer mobility and efficient separation of the photogenerated electron‐hole pairs. Thus, the photocatalytic hydrogen evolution performance of fibrillar CTFs is about twice that of block structure.